The Effect of caffeine on cognitive processes, sleep and sports performance - Radosław Szydłowski; Magdalena Bodera; Hanna Porwolik; Agata Porwolik; Agnieszka Porwolik; Anna Kaźmierska; Anna Hamerla; Julia Gawron (Journal of Education, Health and Sport)
Introduction: Caffeine is one of the most frequently used psychostimulants in the world. It is present in many drinks consumed around the world. Its stimulating effect on the central nervous system has been known for years. Moreover, many athletes take it before competitions to achieve better results. The aim of this study is to present the effect of caffeine on cognitive abilities, sleep and performance in sports.